3D-Printed Porous Tantalum Scaffolds for Bone Regeneration: A Narrative Review of Structural Design, Biological Performance, and Clinical Applications - Michael Lizar; Xingshuang Ma (FaST - Jurnal Sains dan Teknologi (Journal of Science and Technology), 2026)
Bone fractures remain a major clinical challenge in orthopedic surgery, requiring biomaterials that closely mimic the structural and mechanical properties of native bone. Although titanium and its alloys are widely used, their limited porosity and elastic modulus mismatch may compromise osseointegration and long-term implant stability. Three-dimensional (3D)-printed porous tantalum (Ta) scaffolds have emerged as promising alternatives due to their high biocompatibility, corrosion resistance, and osteoconductive potential. This narrative review comprehensively evaluates the structural design, additive manufacturing strategies, mechanical performance, biological interactions, and clinical applications of 3D-printed porous Ta scaffolds for bone regeneration. Particular attention is given to scaffold architecture, pore geometry optimization, and scaffold–cell interactions, including the incorporation of bone marrow–derived mesenchymal stem cells (BMSCs). Advances in additive manufacturing techniques, such as Selective Laser Melting and Laser Engineered Net Shaping, enable the fabrication of highly interconnected porous structures with bone-mimetic mechanical properties. Evidence from in vitro and in vivo studies indicates that pore sizes of 400–600 µm and porosity around 80% provide a favorable microenvironment for cell adhesion, proliferation, and osteogenic differentiation. Functionalization strategies and activation of osteogenic signaling pathways further enhance mineralization and interfacial integration. Overall, the integration of 3D-printed porous Ta scaffolds with regenerative cellular strategies represents a promising approach for bone defect repair, spinal fusion, and joint reconstruction. Continued optimization of scaffold design and validation through long-term clinical studies are essential to facilitate translational application.